Land Archive Management Village-based - Safitri, Dyah (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
Background of the study: In villages, land documents, especially for land that has not been certified or commonly referred to as traditional land, often triggers problems. Customary land, which is often called girik, petok, rincik, ketitir, letter C or others, is not supported by adequate documents. Even if there is in the community, the condition is often problematic, whether it's torn, the paper is fragile, and damaged, or ink that has been difficult to read. Purpose: The purpose of this study is to explore the management of village-based land records through the digitization of land titles stored in villages or villages. Method: The methodology used in this research is through direct assistance to village officials to practice the digitalization and regulation of land records based on archival rules. Findings: The findings of this study are that the archives of the villagers' land are often stored just like that in the village, making them vulnerable to damage, loss and hard to find again. With the rules of archival science and digitizing land records, the process of meeting will be easier again. Conclusion: This research has a theoretical and practical impact. Theoretically provide insight into digitizing vital archives. Whereas practically, if the management of land records can be carried out well, then the potential for land conflicts can be reduced to a minimum.